Rancang Bangun Alat Ukur Kualitas Jaringan Berbasis Raspberry Pi 3 Model B - Sudarsono, Joshua Fernaldy; Sukadarmika, Gede; linawati, linawati (Majalah Ilmiah Teknologi Elektro, 2021)
The Internet has become a necessity for modern society in carrying out its various activities today .The rapid increase in Internet users from year to year shows that people's need for the Internet is increasing .In Indonesia, Internet user growth is predicted to increase by 10.2 percent annually from 2018 to 2023.However, the growth in the number of customers is often not followed by the ability of Internet providers to improve maintenance facilities to maintain the quality of service to their customers .One of the causes is the limitations of the device which is often an obstacle for technicians to do maintenance as soon as possible. This research aims to be able to design and build devices that can be applied as a means of measuring network quality more simply and economically so as to support the mobility of technicians to use and maintain their networks .The devices built on the study are based on the Raspberry Pi 3 Model B. Comparison of device performance measurement results such as battery life, ping, upload and download rate between devices built with laptop usage gives almost the same results. This built lifter has advantages on the side of smaller and lighter dimensions and a much more economical cost.